The efficacy and safety of electrolyzed water against Covid-19 as an alternative hand sanitizer - Rachmat Hidayat; Patricia Wulandari (Medicinski glasnik, 2022)
Aim: To investigate the efficacy of electrolyzed water against viruses and its safety to the skin. Methods: Virus culture was carried out at level-3 Bio-Safety (BSL3) facilities. The test material was prepared at room temperature mixed with one part virus suspension and one organic load. As an antiseptic and disinfectant control, 0.7% formaldehyde was used. Cytotoxic effects of electrolyzed water were performed on Vero cells. In order to assess the safety of electrolyzed water, a skin sensitivity test was conducted for electrolyzed water exposure. Results: Electrolyzed water has a higher value of reduction factor than antiseptic and disinfectant control, formaldehyde, and it was statistically different from control. Cytotoxicity test results on Vero cells showed that electrolyzed water demonstrated safety in Vero cell viability. As many as 58 participants who met the inclusion criteria took electrolyzed water sensitivity test to the skin. The sensitivity test showed that participants with reactions to electrolyzed water were all female, with a mean age of 32.6 years. The patch-test was positive in 3 of 4 participants who reacted to the product. Conclusion: Electrolyzed water is effective as a new antiseptic and disinfectant against viruses and safe for human skin.
Keywords: cell survival; disinfectants; local anti-infective agents; Vero cells; viruses